Determinants of Village Fund Management in Improving Village Development and Economy - Mainatul Ilmi; Mustofa Mustofa (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2020)
Village development as a priority of government programs of regional and national development. In 2018, the percentage of poverty in Jember Regency occupies the 2nd position in East Java.The purpose of the study was to examine and analyze the influence of the competency of village companion, the organizational commitment of village apparatus, and the community's response to the management of village funds, and the influence of village fund management on improvementof village development and economy. The research method uses linear regression. The results show that the competency of village companion has no effect on village fund management; the organizational commitment of village apparatus and community response has a positive effect on village fund management; and village fund management has a positive effect on improvement of village development and economy.